Digital image-based colorimetry analysis of rhodamine b and congo red using compact camera at varying resolutions. - Gabriel Hans N. Loresto, Joan A. De Leon, John Emmanuel R. Gaspar, Adriece Yancy P. Llaguno, Janna Mae R. Morales. 4 0 16; 5
ABSTRACT: Increasing production of synthetic dyes raised environmental and health concerns, prompting the establishment of regulatory policies. Several methods for the determination of the presence of synthetic dyes have been developed but these ,ethods are often costly and time-consuming. Digital image-based colorimetry (DIBC) can provide a cost-efficient approach to the determination of CR and RhB dye content. Using compact cameras in DIBC method offers an inexpensive and simple procedure in comparison to traditional techniques. In this study, calibration curves were constructed using standard solutions of CR (10, 12.5, 15.0, 17.5, and 20.0 ppm) and RhB (1.0, 1.25, 1.50, 1.75, and 2.0 ppm). Additionally, unknown solutions for both compounds were prepared for analysis. Results indicate a notable difference in sensitivity between DIBC and UV-vis analysis for both CR and RhB. However, when comparing DIBC analyses at resolutions of 3MP and 7MP with UV-vis analysis, no significant differences were observed in the Limit of Detection (LOD), Limit of Quantification (LOQ) for both dyes. Ultimately, calculated concentrations of spiked samples between the two methods have no significant difference for both dyes. These findings indicate the potential for utilizing readily available compact cameras using 3MP and 7MP resolution in colorimetric analysis, offering a cost-effective and accessible alternative to traditional spectrophotometric techniques.
Undergraduate Thesis : (bachelor of Science in Chemistry) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2